2020
DOI: 10.1186/s41073-020-00096-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying professionalism in peer review

Abstract: Background The process of peer-review in academia has attracted criticism surrounding issues of bias, fairness, and professionalism; however, frequency of occurrence of such comments is unknown. Methods We evaluated 1491 sets of reviewer comments from the fields of “Ecology and Evolution” and “Behavioural Medicine,” of which 920 were retrieved from the online review repository Publons and 571 were obtained from six early career investigators. Comment sets were coded for the occurrence of “unprofessional comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 17 publications
(18 reference statements)
0
43
0
3
Order By: Relevance
“…Editors' preference to tone down potentially offensive or discriminatory remarks is also comprehendible, particularly given current pressures to retain reviewers, the non-trivial rate of unprofessional reviews and their potential negative impact on authors' productivity and wellbeing. 7,22,47,48 This course of action has also been specifically advised in cases discussed by the COPE Forum. 49 Removal of identifying information is also likely reflective of stricter enforcement of blinding policies.…”
Section: Discussionmentioning
confidence: 99%
“…Editors' preference to tone down potentially offensive or discriminatory remarks is also comprehendible, particularly given current pressures to retain reviewers, the non-trivial rate of unprofessional reviews and their potential negative impact on authors' productivity and wellbeing. 7,22,47,48 This course of action has also been specifically advised in cases discussed by the COPE Forum. 49 Removal of identifying information is also likely reflective of stricter enforcement of blinding policies.…”
Section: Discussionmentioning
confidence: 99%
“…For the situations examined in the current study, one could argue that fixing spelling and grammatical errors is benign, or even a necessary copy-editing step prior to publication of reviews. Editors' preference to tone down potentially offensive or discriminatory remarks is also comprehendible, particularly given current pressures to retain reviewers, the non-trivial rate of unprofessional reviews and their potential negative impact on authors' productivity and wellbeing [7,21,42,43]. This course of action has also been specifically advised in cases discussed by the COPE Forum [44].…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of how pervasive the problem is in the field of ecology and evolution, based on 1491 sets of reviewer comments, Gerwing et al. (2020) found that 10–35% of peer reviews provided to authors included demeaning language, while 43% contained at least one unprofessional comment about the author or the author's work. I have not found a similar study in agricultural economics.…”
Section: Inclusion and The Scholarly Merit System: How Can They Be Almentioning
confidence: 99%